ANALISA STRUKTUR JEMBATAN BETON BERTULANG SEI KEHAM DI DESA LEBAK MANTAN KECAMATAN MUARA WEIS KABUPATEN KUTAI KARTANEGARA - RATIH FITRIANI, DEWI (KURVA S JURNAL MAHASISWA, 2013)
The bridge is a building of road complement which has a function as traffic connector tools which are cut at both road corners caused by many obstacles.            The Sei Keham bridge originally was a wooden bridge used by local people as facilities to connect between villages.  Therefore, it needs increasing the bridge capacity to be reinforced concrete bridge.                Analysis  of The reinforced concrete bridge calculations uses the   rule of SNI T-02-2005 about loading on the bridge. The bridge range is 6 meters long and 6 meters wide within 0,5 meters wide on each side of the pavement. So that, the bridge is 7 meters wide totally. Based on calculations analysis, it may be concluded that the floor slab uses reinforcement D 13-150 for flexural negative steel,  D 16-150  for flexural positive steel. Pavement uses reinforcement D 16-150. Backrest uses  reinforcement 12 poles Ø 12. Tread plate for transverse and longitudinal directions uses reinforcement D 16-150. Girder uses reinforcement 24 D 32. Diaphragms uses reinforcement 2 D 25 and pile foundation uses 30 cm diameter with a length of 22 meters.